Guide to load analysis for durability in vehicle engineering - Johannesson, Par.; Speckert, Michael; Dressler, Klaus (Chichester, West Sussex : John Wiley & Sons Inc., 2014)
"Covers the use of established computational methods, such as finite element method (FEM) and multi body simulation (MBS), and their appropriate use within load analysis for durability"--
pt. I. Overview -- pt. II. Methods for load analysis -- pt. III. Load analysis in view of the vehicle design process.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Trucks -- Dynamics; Finite element method; Trucks -- Design and construction; Electronic books